THE CONSTRUCTION OF INTER-FAITH DIALOGUE AS A CONFLICT PREVENTIVE EFFORT: A CONCEPTUAL ANALYSIS - ROBINHOT SIHOMBING; RAMSIDA N SIBURIAN (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
Inter-religious dialogue has a critical function internally and externally. Such dialogue offers a new reality for the advancement of living together in society, because there is a dynamic process in religious understanding and its application. This study aims to look at dialogue between religious communities in an effort to prevent conflict. The research was carried out using a qualitative approach. Secondary data was extracted through document analysis of various books, religious scriptures, and documents related to this research. The data were analyzed qualitatively (thematically) which resulted in the following findings: (i) inter-religious dialogue was carried out through social activities, (ii) there was a habit and awareness of the community to carry the burden together in mutual cooperation, (iii) support from village leaders and religious leaders. . The results of this study are discussed with various theories and the results of previous research, and can be used as a reference for creating peace, harmony, tranquility, harmony and mutual respect for the principle of togetherness in a pluralistic society.